The Influence of Leadership Attitudes on Employee Work Discipline in the Economic and Development Administration Bureau of the Regional Secretariat of South Sulawesi Province - Akib, Haedar; Taufiq, Muhammad; Saleh, Sirajuddin (Pinisi Journal of Education and Management, 2023)
The quality of human resources is very important in an agency, the resources in question are employees, to maintain this quality you need a leader who has quality behavior. Direction for the work carried out by employees in an agency must be given by a competent leader to create good work discipline for the employees. This research aims to determine the description of leadership attitudes, the description of employee work discipline, and the influence of leadership attitudes on employee work discipline. This research is quantitative research with a symmetric associative design that uses descriptive and inferential statistical science tools. The population of this study was all 55 employees and 48 people based on the Krejcie table using a random sampling technique. The data collection techniques used were questionnaires and documentation. The data analysis techniques used are descriptive and inferential statistical analysis. The test results show that the leadership's attitude is in the very good category and employee work discipline is in the very good category. In the product-moment correlation test, the relationship between variables is strong and there is an influence between the two variables. Based on the results of simple linear regression analysis, it was concluded that there was a positive and significant influence on leadership attitudes on employee work discipline in the Bureau of Economics and Development Administration of the Regional Secretariat of South Sulawesi Province